2012
DOI: 10.2139/ssrn.2179528
|View full text |Cite
|
Sign up to set email alerts
|

Export Dynamics and Sales at Home

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
91
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(101 citation statements)
references
References 67 publications
8
91
2
Order By: Relevance
“…Manova, 2008;Berman and Héricourt, 2010;Minetti and Zhu, 2011). A collapse of domestic sales may aggravate a firm's liquidity shortages or credit constraints and thus limit its ability to bear the costs for selling abroad, as found by Berman et al (2015). Using a sample of Italian manufacturing firms, we estimate how these correlation varies over the period 2001-2012 and assess what are their determinants.…”
Section: Introductionmentioning
confidence: 99%
“…Manova, 2008;Berman and Héricourt, 2010;Minetti and Zhu, 2011). A collapse of domestic sales may aggravate a firm's liquidity shortages or credit constraints and thus limit its ability to bear the costs for selling abroad, as found by Berman et al (2015). Using a sample of Italian manufacturing firms, we estimate how these correlation varies over the period 2001-2012 and assess what are their determinants.…”
Section: Introductionmentioning
confidence: 99%
“…As a robustness check, we have also computed instruments using shares calculated over the period 1996–2009 as in Berman et al . (). Results are very similar.…”
mentioning
confidence: 97%
“…The BACI data set is constructed using bilateral trade data at HS6-digit level from COMTRADE. It can be downloaded at http://www.cepii.fr/CEPII/en/bdd_modele/presentation.asp?id=1 (last accessed: 11 December 2014).10 As a robustness check, we have also computed instruments using shares calculated over the period 1996-2009 as inBerman et al (2012). Results are very similar.© 2015 Royal Economic Society.…”
mentioning
confidence: 99%
“…Particularly, this relationship is stronger when domestic demand is falling rather than increasing. Berman et al (2015) found that the reverse was true: exogenous shocks in firm-level exports are positively related to domestic sales. Vannoorenberghe (2012) presented a framework in which firms responded to shocks in the domestic market by adjusting sales in external markets and provided strong evidence that the domestic and export markets are negatively correlated at the firm level.…”
mentioning
confidence: 99%